Gallium nanoparticles along with low-dose gamma radiation modulate TGF-β/MMP-9 expression in hepatocellular carcinogenesis in rats - Fatma SM Moawed; Sawsan M El-Sonbaty; Somaya Z Mansour (Tumor Biology)
Combining chemotherapy with radiotherapy potentiates the outcome of cancer treatment for the more comprehensive attack. In the current study, we continued to assess the therapeutic efficaciousness of the newly synthesized gallium nanoparticles (GaNPs) combined with low level of gamma radiation (IR), on the incidence of diethylnitrosamine (DEN)–induced hepatocellular carcinoma (HCC) in rats. Oral administration of GaNPs (1 mg/Kg b.wt.) 5 times per week for 6 weeks combined with IR to rats treated with DEN (20 mg/Kg b.wt. 5 times per week for 6 weeks) significantly reduced serum levels of alpha-fetoprotein (AFP), aspartate transferase (AST), alanine transferase (ALT), and gamma-glutamyltransferase (GGT). In addition, the immunoblotting results of matrix metalloproteinase-9 (MM-9) showed a marked downregulation of protein expression along with a significant decrease in the hepatic level of transforming growth factor β (TGF-β). Furthermore, GaNPs and/or low dose of radiation significantly elevated the level of caspase-3 gene transcript accompanied with evoked DNA fragmentation in rats treated with DEN. The ameliorative effect of GaNPs and IR well appreciated with the histopathological alteration finding in DEN groups. It can be concluded that the combination of GaNPs and/or IR can serve as a good therapeutic agent for the treatment of HCC, which ought to attract more studies.